Determinants of Employee Performance: Job Involvement, Job Characteristics, and Organizational Commitment (Al Dzahab, 2026)
Purpose: This study aims to analyze the effect of job involvement, job characteristics, and organizational commitment on employee performance at the Housing, Settlement, and Land Affairs Office of Sungai Penuh City.Design/Methodology/Approach: This study employed a quantitative survey approach, distributing questionnaires to 49 employees. Data were analyzed using IBM SPSS 26.0 through validity and reliability tests, multiple linear regression analysis, t-tests, F-tests, and the coefficient of determination (R²).Findings: The results reveal that job involvement, job characteristics, and organizational commitment partially have a positive and significant effect on employee performance. Simultaneously, all independent variables significantly influence employee performance, indicated by an F-test significance value of 0.000. The coefficient of determination (R²) of 0.722 indicates that the three variables explain 72.2% of the variance in employee performance, while other factors outside the research model explain 27.8%.Research Implications: The findings suggest that organizations, particularly public institutions, should strengthen employee involvement, improve job design, and enhance organizational commitment to achieve optimal and sustainable employee performance.